2011
DOI: 10.1021/ic101994k
|View full text |Cite
|
Sign up to set email alerts
|

Trifluorosulfane Ligand as an Analogue of the Nitrosyl Ligand: Highly Exothermic Fluorine Transfer Reactions from Sulfur to Metal in the Chemistry of SF3Metal Carbonyls of the First Row Transition Metals

Abstract: The variety of known very stable PF(3) metal derivatives analogous to metal carbonyls suggests the synthesis of SF(3) metal derivatives analogous to metal nitrosyls. However, the only known SF(3) metal complex is the structurally uncharacterized (Et(3)P)(2)Ir(CO)(Cl)(F)(SF(3)) synthesized by Cockman, Ebsworth, and Holloway in 1987 and suggested by electron counting to have a one-electron donor SF(3) group rather than a three-electron donor SF(3) group. In this connection, the possibility of synthesizing SF(3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…The frontier orbital analysis revealed that the electron pair is reflected by the HOMO (Figure 2). Hence, the λ 4 ‐trifluoro sulfanyl ligand can be considered as an one‐electron donor or two‐electron donor, when the sulfanyl group is considered to be anionic [21] …”
Section: Resultsmentioning
confidence: 99%
“…The frontier orbital analysis revealed that the electron pair is reflected by the HOMO (Figure 2). Hence, the λ 4 ‐trifluoro sulfanyl ligand can be considered as an one‐electron donor or two‐electron donor, when the sulfanyl group is considered to be anionic [21] …”
Section: Resultsmentioning
confidence: 99%
“…The experimentally observed pseudo‐square‐pyramidal (trigonal‐bipyramidal) geometry at sulfur is consistent with a one‐electron‐donor ligand. In contrast, a tetrahedral arrangement at the sulfur atom is in accordance with a formal 3‐electron donation to the metal center . Calculations on the experimentally known complexes trans ‐[Ir(Cl)(F)(SF 3 )(CO)(PEt 3 ) 2 ] ( 119 ) cis , trans ‐[Rh(F) 2 (SF 3 )(CO)(PEt 3 ) 2 ] ( 122 ), and trans ‐[Pt(F)(SF 3 )(PR 3 ) 2 ] [R= i Pr ( 125 a ), Cy ( 125 b )] revealed a pseudo‐square‐pyramidal (trigonal‐bipyramidal) coordination of the sulfur atom, which was also suggested based on variable temperature NMR spectroscopic data …”
Section: Sulfur(iv) Compoundsmentioning
confidence: 99%
“…DFT studies on fluoride migration reactions in trans ‐[Ir(Cl)(F)(SF 3 )(CO)(PEt 3 ) 2 ] ( 119 ), [M(SF 3 )(CO) n ] (M=V ( 131 a ), Ta ( 131 b ), n =5; M=Mn ( 131 c ), Re ( 131 d ), n =4; M=Co ( 131 e ), Ir ( 131 f ), n =3) and [CpM(SF 3 )(CO) n ] (Cp=η 5 ‐C 5 H 5 ; M=Cr ( 132 a ), W ( 132 b ), n =2; M=Fe ( 132 c ), Os ( 132 d ), n =1; M=Ni ( 132 e ), Pt ( 132 f ), n =0) to form the respective {[M](F)(SF 2 )} complexes suggest an instability of SF 3 ligands at first‐ and third‐row transition‐metal derivatives . Exceptional cases are both iridium‐based compounds, for which a fluoride shift in [Ir(SF 3 )(CO) 3 ] ( 131 f ) is almost thermoneutral and is clearly energetically not favored in trans ‐[Ir(Cl)(F)(SF 3 )(CO)(PEt 3 ) 2 ] ( 119 ) .…”
Section: Sulfur(iv) Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical studies suggest that metal carbonyl trifluorosulfane derivatives such as M(CO) n (SF 3 ) (n = 5, M = V, Ta; n = 4, M = Mn, Re; n = 3, M = Co) with tetrahedral three-electron donor SF 3 ligands are strongly disfavored thermochemically with respect to a fluorine shift from sulfur to metal to give isomeric M(CO) n (F)(SF 2 ) complexes. 22,23 Only Ir(CO) 3 (SF 3 ), in which the SF 3 group is a pseudo trigonal bipyramidal oneelectron donor ligand rather than a tetrahedral three-electron donor ligand, has a chance of being viable toward fluorine shift to give the isomeric Ir(CO) 3 (F)(SF 2 ) derivative. These theoretical studies suggest that the SF 3 ligand, at least as a tetrahedral threeelectron donor, is too strong a fluorinating agent for trifluorosulfane metal carbonyl complexes to be viable.…”
Section: Introductionmentioning
confidence: 99%